Comparative Study between Ultrasound-Guided Quadratus Lumborum Block Type 2 Versus Lumbar Epidural Analgesia as a Perioperative Analgesic Technique for Pelvic Cancer Surgeries - Elwakil, Mohammad; Tharwat, John; Abbas, Dina; Elwaseef, Mohammad; Elgendy, Sameeh (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: The effect of the quadratus lumborum block (QLB) is believed to result from a spread of LA from its lumbar deposition cranially into the thoracic paravertebral space.The aim of this study is to compare the analgesic efficacy of an Ultrasound-guided quadrates lumborum type II block versus lumbar epidural analgesia or conventional analgesia after pelvic cancer surgeries regarding intraoperative fentanyl consumption, postoperative pain scores and morphine consumption in the first 24 hours. Methods: This study was conducted on 90 patients of American Society of Anesthesia (ASA) physical status II scheduled for elective pelvic cancer operations. Patients were randomized into three equal groups of 30 patients: Group Q: received bilateral QLB by 20ml of 0.25% bupivacaine in each side, Group E: received continuous lumbar epidural block analgesia ((0.125 % bupivacaine at infusion rate of 6ml/hour for 24 hours). Group C (Control group): were transferred to operation room without further intervention. Results: End tidal sevoflurane was significantly decreased in group Q than group C and in group E than group C at all time measurements. VAS at 0.5, 1, 8. 16 and 24 hours was significantly increased in group C than Group Q and group E. Time to first rescue dose of morphine was significantly increased in Group E than Group Q (P1 <0.001) and was significantly decreased in group C than Group Q (P2 <0.001) and was significantly decreased in group C than Group E (P3 <0.001). Total dose of morphine in 1st 24 hours was significantly increased at group C than group Q and group E (P <0.001) but there was an insignificant difference between Group Q and E. Conclusion: When compared to the control group, QLB and epidural block resulted in decreased VAS, intraoperative sevoflurane and fentanyl use and postoperative morphine consumption with a greater level of patient satisfaction. Epidural block, on the other hand, resulted in less intraoperative sevoflurane usage than QLB.